1970
DOI: 10.1002/qj.49709640707
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of linear lee wave theory for the stratosphere

Abstract: SUMMARYCertain theoretical features of high altitude lee waves for some simple two-dimensional models are described. It is shown that some of these allow an intense local radiation of lee waves in a nearly vertical beam into the high stratosphere (similar to the leakage upwards of short radio waves in a familiar electromagnetic theory), Some associated quasi-resonance phenomena are noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…As it has been already mentioned, for sufficiently low velocities (U 0 ≤30 ms −1 ), the major differences between the hydrostatic and non-hydrostatic solutions take place in the vicinity of the quasi-resonant peaks, where, along with the hydrostatic component of the solution, the amplification of the short, partially trapped waves takes place (Berkshire and Warren, 1970). One can see from Figs.…”
Section: Three-layer Solutionmentioning
confidence: 51%
See 1 more Smart Citation
“…As it has been already mentioned, for sufficiently low velocities (U 0 ≤30 ms −1 ), the major differences between the hydrostatic and non-hydrostatic solutions take place in the vicinity of the quasi-resonant peaks, where, along with the hydrostatic component of the solution, the amplification of the short, partially trapped waves takes place (Berkshire and Warren, 1970). One can see from Figs.…”
Section: Three-layer Solutionmentioning
confidence: 51%
“…It was found that partial reflection of wave energy by individual layers with different static stability and/or wind velocity can produce a strong influence on the flow field in the free atmosphere (Scorer, 1949;Blumen, 1965;Eliassen and Palm, 1961;Berkshire and Warren, 1970). Some aspects of this problem were considered in many of investigations (see reviews by Queney et al, 1960;Kozhevnikov, 1970;Smith, 1979;Röttger, 2000), principally in the framework of linear models permitting one to account for actual really observed vertical distributions of atmospheric characteristics, including those at large altitudes (Palm and Foldvik, 1960;Berkshire, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…The tropopause acting as a ''leaky'' lid can be important for lee waves in sheared flow (e.g., Keller 1994) and for propagating gravity waves generated by convection (Lane and Zhang 2011). As the troposphere 2 stratosphere stability difference becomes greater, less energy leaks through and the tropopause begins to act more like a rigid lid (e.g., Berkshire and Warren 1970). Stable layers functioning as reflective surfaces similar to rigid lids have also been noted in density current simulations (Xue 2002) and for elevated inversions in downslope windstorm simulations (e.g., Smith and Skyllingstad 2011).…”
Section: Introductionmentioning
confidence: 98%
“…In the last decade, interest has been shown in these evanescent modes produced by a long terrestrial mountain ridge, and attention has been directed toward a stratosphere-troposphere model in which the troposphere is divided into an upper and lower region with differing stabilities in each. This theory has been discussed by Berkshire and Warren [1970] and Berkshire [1975], while in Berkshire and Pickersgill [1978] this model is adapted to consider a troposphere with increasing or decreasing stability with height and a stably stratified stratosphere. Pirraglia [1976] has investigated the theory of trapped Martian lee waves produced by an isolated crater of diameter 100 km in the northern winter.…”
Section: Introductionmentioning
confidence: 99%